Network analysis and tactical behaviour in soccer small-sided and conditioned games: influence of absolute and relative playing areas on different age categories - Moreira, P. E. D.; Barbosa, G. F.; Murta, C. D. C. F.; Pérez Morales, J. C.; Bredt, S. D. G. T.; Praça, G. M.; Greco, P. J. (International Journal of Performance Analysis in Sport, 2020)
This study aimed to compare the effect of manipulating the absolute and relative area of SSCG on players` behaviour. 36 players were selected from the U-13 and U-14 category. The SSCG were played in three different formats: 3 vs. 3 (36 × 27 m, 162 m2), 3 vs. 3 + 1 (36 × 27 m, 139 m2), and 3 vs. 3 + 1 large (40 × 29 m, 162 m2). Tactical behaviour and network properties were assessed using the FUT-SAT and the Social Network Analysis, respectively. A two-way ANOVA was used to compare the dependent variables between the different SSCG and ages. Results showed that U-14 players performed more actions of offensive coverage (p = 0.01; small-to-medium effect) and presented a lower dispersion of the eigenvector centrality (p = 0.002; small effect). Moreover, increases in the relative playing area induced an increase of offensive coverage actions (p = 0.01; medium effect). The simultaneous reduction of absolute and relative playing area induced a higher frequency of offensive unity (p = 0.02; medium effect), increased the level of interaction between players (p = 0.001; large effect). We conclude that, for young players, U-13 and U-14 category, it is important to reduce the area of SSCG during training sessions to increase tactical performance.